Developing Children’s Cooperation Skills through Traditional Bakiak Games: Mengembangkan Keterampilan Kerja Sama Anak-Anak Melalui Permainan Tradisional Bakiak - Bariyah, Khoirul; Rocmah, Luluk Iffatur (Universitas Muhammadiyah Sidoarjo, 2025)
Specific Background: In modern times, digital games reduce children’s opportunities to develop cooperation and gross motor skills. Gap: Few studies focus on how the traditional “bakiak” game improves children’s cooperative abilities in early childhood education. Aims: This study aims to explore how the use of bakiak games can foster cooperation skills among group B kindergarten students. Results: The findings show that participation in bakiak games increases children’s teamwork, communication, and coordination. Teachers observe significant improvement in collaborative play. Novelty: The research highlights the integration of local traditional games as effective learning tools for character development. Implications: The study implies that educators can utilize traditional games to promote socio-emotional learning in early childhood settings. Highlights:• Strengthening cooperation through cultural games• Integrating traditional play in early education• Supporting social-emotional development Keywords: Traditional Games, Cooperation, Early Childhood, Social Development, Bakiak